ASUHAN KEPERAWATAN PADA KLIEN DIABETES MELITUS DENGAN MASALAH KETIDAKSTABILAN KADAR GLUKOSA DARAH DI KELURAHAN PAMEGARSARI KABUPATEN BOGOR - Rizky Amallia (2023)
Background : Diabetes is a disorder of the endocrine system, namely metabolism due to damage to insulin secretion or work or both which results in blood sugar levels in the body not being at normal levels.Objective : Obtaining real experience from nursing care to clients with diabetes mellitus with nursing problems of blood glucose level instability in the Pamegarsari sub-district, Bogor district, which is carried out using nursing care including assessment, nursing diagnosis, nursing intervention, nursing implementation and nursing evaluation.Method : This research method uses qualitative which tends to use analysis in its research and is described descriptively with a case study research design in carrying out nursing care for clients with diabetes mellitus with problems of unstable blood glucose levels in Pamegarsari Village, Bogor Regency. Data collection was carried out by means of interviews, observation and physical examination.Results : The nursing problem found in this case is the instability of blood sugar levels associated with insulin resistance, non-adherence associated with side effects of treatment / treatment programs, impaired skin integrity associated with changes in pigmentation.Conclusion : It is hoped that future research can better carry out nursing care for clients with diabetes mellitus in order to obtain the intended results in accordance with the nursing problems that clients experience.